2017
DOI: 10.3892/ijo.2017.3969
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-556-3p promotes human bladder cancer proliferation, migration and invasion by negatively regulating DAB2IP expression

Abstract: MicroRNAs (miRNAs) play critical roles in tumorigenesis and metastasis by negatively regulating gene expression through complementary binding to the 3'-untranslated region of target mRNAs. The role of miRNAs in expression of the tumor suppressor DAB2IP in bladder cancer (BC) remains unknown. The aim of the present study was to identify miRNAs targeting DAB2IP and determine their expression and function in BC. We predicted candidate miRNAs targeting DAB2IP using TargetScan software. Dual-luciferase reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…MiR-217 has been reported to inhibit the proliferation and migration of bladder cancer cells through targeting KMT2D 36 . MiR-556-3p can exacerbate the capacity of proliferation, migration and invasion of human bladder cancer cells via negatively regulating the expression of DAB2IP 37 . Xie et al have revealed that downregulation of miR-532-5p can signi cantly promote the proliferation and invasion of bladder cancer cells by activating the HMGB3/Wnt/β-catenin signaling pathway 38 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-217 has been reported to inhibit the proliferation and migration of bladder cancer cells through targeting KMT2D 36 . MiR-556-3p can exacerbate the capacity of proliferation, migration and invasion of human bladder cancer cells via negatively regulating the expression of DAB2IP 37 . Xie et al have revealed that downregulation of miR-532-5p can signi cantly promote the proliferation and invasion of bladder cancer cells by activating the HMGB3/Wnt/β-catenin signaling pathway 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs of the miR-92a family were reported to target DAB2IP in multiple tumors [ 86 , 91 , 92 , 93 ]. DAB2IP inhibition by miR-556 in bladder and esophageal cancer fosters cells proliferation and sustains tumor progression via aberrant Ras-MAPK signaling activation [ 94 , 95 ]. Intriguingly, miR-556 was detected in the plasma of bladder cancer patients, suggesting that this miRNA could repress DAB2IP in a cell non-autonomous manner.…”
Section: Post-transcriptional Inhibition Of Rasgaps In Cancermentioning
confidence: 99%
“…miRNAs may modulate the expressions of different coding genes by inducing translational repression or the degradation of target mRNAs via base pairing with the specific sequences in the 3′UTRs . In fact, the deregulations of many carcinogenic or antitumor miRNA have been verified to be associated with tumor initiation and progression . For example, miR‐133b/135a induced human renal carcinoma cell apoptosis via the JAK2/STAT3 signaling pathway; miR‐21 promoted triple‐negative breast cancer cell proliferation and invasion via targeting PTEN; and miR‐4317 suppressed human gastric cancer cell proliferation via the regulation of ZNF322 .…”
Section: Introductionmentioning
confidence: 99%